2015
DOI: 10.1371/journal.pone.0122055
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ankylosing Spondylitis and the miR-146a and miR-499 Polymorphisms

Abstract: miRNAs are small, non-coding RNAs that regulate the expression of multiple target genes at the post-transcriptional level. Single-nucleotide polymorphisms (SNPs) in miRNA sequences may alter miRNA expression and have been implicated in the pathogenesis of multiple forms of arthritis, including rheumatoid arthritis (RA) and osteoarthritis. The present study explored the association between ankylosing spondylitis (AS) and two single nucleotide polymorphisms (SNPs), miR-146a rs2910164G>C and miR-499 rs3746444T>C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
0
41
2
Order By: Relevance
“…As for the miR - 146a SNP, some associations with pathogenesis of rheumatic diseases have been described especially for patients with ankylosing spondylitis in a Han Chinese population (Xu et al 2015). However, this SNP has not been reported to be associated with RA in either Asian or Caucasian populations (Chatzikyriakidou et al 2010; El-Shal et al 2013; Zhou et al 2015; the present study).…”
Section: Discussionmentioning
confidence: 99%
“…As for the miR - 146a SNP, some associations with pathogenesis of rheumatic diseases have been described especially for patients with ankylosing spondylitis in a Han Chinese population (Xu et al 2015). However, this SNP has not been reported to be associated with RA in either Asian or Caucasian populations (Chatzikyriakidou et al 2010; El-Shal et al 2013; Zhou et al 2015; the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al () investigated the connection between AS and two single nucleotide polymorphisms (SNPs), miR‐146a rs2910164G>C, and miR‐499 rs3746444T>C, in a Han Chinese population. A case‐control study including of 102 subjects with AS and 105 healthy controls was designed.…”
Section: Biogenesis Of Mirnasmentioning
confidence: 99%
“…The two miRNA polymorphisms had no association with the AS activity level. As a conclusion, Xu et al (2015) 18 through their research found that the miR-146a rs2910164 variant was related with increased risk of AS at both the allelic and genotypic stages. The G allele and GG genotype were more prevalent in the patients than in the control group.…”
Section: Polymorphisms Of Mirnas and Their Target Genes In Asmentioning
confidence: 89%
“…According to the previous statement a quite interesting research was conducted by Xu et al (2015) 18 between March 2013 and April 2014 in a Chinese province researching the possibility of a significant correlation between SNPs -located in miR-14a and miR-499-and ankylosing spondylitis. The study was composed by two groups.…”
Section: Polymorphisms Of Mirnas and Their Target Genes In Asmentioning
confidence: 99%